2011
DOI: 10.1080/03235400903395369
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal and high-performance liquid chromatography analysis of the crude extracts ofAcorus calamus, Tinospora cordifoliaandCelestrus paniculatus

Abstract: The antifungal activity of methanolic crude extracts of Acorus calamus, Tinospora cordifolia and Celestrus paniculatus was investigated against Alternaria solani, Curvularia lunata, Fusarium sp., Bipolaris sp. and Helminthosporium sp. at different concentrations (1000, 2000, 3000, 4000 and 5000 mg/ml). At 5000 mg/ml, crude extract of T. cordifolia is found to be highly effective against Helminthosporium sp. followed by A. calamus against A. solani. On the other hand, at 5000 mg/ml, C. paniculatus showed better… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
(19 reference statements)
2
8
0
Order By: Relevance
“…The result were in accordance with the findings of Nguyen et al,(2013) who reported that among the plant extract tested in vitro, garlic bulb extract each at 5,10,15% were best in inhibiting the mycelial growth of A. solani. Singh et al, (2010) also reported that Acorus calamus (Sweet flag) crude extract at 5000 μg/ml is found to be highly effective against Alternaria solani. Some of the aqueous plant extracts under in vitro revealed that higher doses were relatively more efficient than the lower doses.…”
Section: Effect Of Plant Extracts On the Growth And Sporulation Of Amentioning
confidence: 99%
“…The result were in accordance with the findings of Nguyen et al,(2013) who reported that among the plant extract tested in vitro, garlic bulb extract each at 5,10,15% were best in inhibiting the mycelial growth of A. solani. Singh et al, (2010) also reported that Acorus calamus (Sweet flag) crude extract at 5000 μg/ml is found to be highly effective against Alternaria solani. Some of the aqueous plant extracts under in vitro revealed that higher doses were relatively more efficient than the lower doses.…”
Section: Effect Of Plant Extracts On the Growth And Sporulation Of Amentioning
confidence: 99%
“…The dry extracts were then collected into a small beaker and labeled based on the organic solvents used. The extracts then were kept in chillers (Chill-300, Protech) at 4˚C for further use slight modification from [6] and [7].…”
Section: Plant Materialsmentioning
confidence: 99%
“…Tannins have been reported to have several pharmacological activities such as spas- molytic activity in smooth muscle cells [50]. Gallic acid has antineoplastic and bacteriostatic activities and anticancer properties in prostate carcinoma cells [28], and anti-inflammatory and antibacterial activity [46]. The present study revealed that gallic acid is in range from 1.64 mg/100 g in C. cornigera parts to 20.35 mg/100 g in C. endivia.…”
Section: Discussionmentioning
confidence: 71%